If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -5t = 7t Solving 3s + -5t = 7t Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '5t' to each side of the equation. 3s + -5t + 5t = 7t + 5t Combine like terms: -5t + 5t = 0 3s + 0 = 7t + 5t 3s = 7t + 5t Combine like terms: 7t + 5t = 12t 3s = 12t Divide each side by '3'. s = 4t Simplifying s = 4t
| -6+9=21 | | 84=4n | | 2x+3.75=7x | | 2x^3-15X^2=2x | | 2x-b+8=5b+4 | | h(x)=2x+4 | | 2532500/x/1277.59=27.68 | | z+2(4+z)=3z+8 | | (3x^4y^3)(9x^2y^6)= | | 10y=2x+5 | | (3-2g)(7-g)=0 | | 2(R+10)=68 | | 15x^3y^11= | | ax+3b=9b | | 0=k-4+4 | | -750c^5+162c^2=0 | | 5x=3x-17 | | 2+6x+2=4 | | (3xy^10)(5x^2y)= | | x+3=8x-4 | | w^2-33w=0 | | m/n-7 | | 6-(2x-4)+x=3 | | k^2-15k=0 | | 5x+3-8=12 | | 7(1+x)=-147 | | 20m^2-9m=0 | | 7(1+x)=-146 | | 6(6-8x)=4(6-10x) | | j^2-28j=0 | | -3x+7+7x+7=15 | | -4(n+4)=-24 |